AGRICULTURE, RIGHT TO FOOD AND BIOECONOMY - Rocha Rodrigues, Romário; Machado de Oliveira, Ariane Maria (A Economia em Revista - AERE, 2022)
This work aimed to analyze how the bioeconomy contributes to modify the food system, making it sustainable. Surveys carried out internationally demonstrate the concern of analysts with the map of hunger that will increase due to Covid-19, as well as the megatrends that will increase the demand for food. The challenge will be to implement an economic model that changes the food system. The bioeconomy will allow focusing on sustainable alternatives regarding the use of natural and biotechnological resources and the form of economic organization, so as not to compromise socio-biodiversity. Through bibliographical analysis, it is concluded that the exploitation of biotechnology and biological resources will place Brazil in the focus of the production of products, inputs and food, attracting investors to the domestic market, making it an important player in the production chain. Consequently, it will expand regional markets, contributing to the reduction of food insecurity in the country.